2017
DOI: 10.5812/semj.14520
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Age at Menarche and Primary Dysmenorrhea in Female Students of Shiraz Schools

Abstract: Background: Dysmenorrhea is one of the most common gynecological problems. This study aimed to determine the relationship between age at menarche and painful menstruation among female students of Shiraz schools. Methods: This cross sectional study was conducted on 2000 female students. For data collection, a researcher-made questionnaire was applied. Data were analyzed using statistical tests in SPSS version 21. Results: About 69.3% of the participants had experienced at least 1 episode of menstrual bleeding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 7 publications
2
17
0
2
Order By: Relevance
“…In a study by Muluneh et al in North-West Ethiopia in 2018, early age at menarche was associated with an increase in the prevalence of dysmenorrhea [16]. Akbarzadeh et al reported a significant association between age at menarche and dysmenorrhea onset [17]. On the other hand, Kural et al could not find such a correlation [18].…”
Section: Discussionmentioning
confidence: 96%
“…In a study by Muluneh et al in North-West Ethiopia in 2018, early age at menarche was associated with an increase in the prevalence of dysmenorrhea [16]. Akbarzadeh et al reported a significant association between age at menarche and dysmenorrhea onset [17]. On the other hand, Kural et al could not find such a correlation [18].…”
Section: Discussionmentioning
confidence: 96%
“…Another factor that affects the incidence of dysmenorrhea in female national athletes in Indonesia is early menarche. Early menarche is considered the most important sign of puberty, which predicts the process of adolescent puberty and the onset of fertility (41). Early menarche occurs before the age of 12 (42).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, since it is important to know how to enter the process of adolescence and how to overcome its ups and downs by adolescents, families should get acquainted with the time and trends of menarche and factors affecting it in order to provide their children with the right decisions in a timely manner [47]. Training issues, especially support of the family, can reduce the stresses and menstrual disorders of the adolescent girls [48], given that the main aim of this project was to study the prevalence of menarche, early and late menarche. Therefore, the factors affecting adolescents' psychological problems have not been fully evaluated.…”
Section: Discussionmentioning
confidence: 99%